An investigation into Grade R teachers' experiences of implementing numeracy in Grade R - Barnard, Elna (Rhodes University, Faculty of Education, Department of Education, 2011)
This research study investigates how selected Grade R teachers implement numeracy in their classrooms, based on their experiences, personal beliefs and perceptions. This study adopts the view that a teacher's practice is not only informed on what she believes about her learners, but also on how she organises her classroom environment and her own teaching practice. However, the teacher cannot be divorced from the political and historical background of Early Childhood Development (ECD), as these factors have an impact on her numeracy implementation. Integrated in this research study is thus not only a comprehensive historical analysis of the historical and political background of ECD, but also an in-depth look at the complex curriculum road the Grade R teacher had to travel over the past twelve years. The aim of this case study is to understand and describe what is happening in Grade R classrooms when numeracy is implemented, as well as identifying possible barriers which Grade R teachers may experience in implementing numeracy. The author utilized an adapted Interactive Qualitative Analysis Framework to explore Grade R teachers' views and experiences. Open-ended focus group interviews were used to develop a framework for individual interviews. This interview framework guided the data collection of nine audio-video tapes of classroom activities and nine semi-structured individual interviews. Analysis of the individual interviews revealed each teacher's understanding as well as her perceptions and needs regarding the implementation of numeracy in her classroom. The transcriptions of the individual interviews were compared to the audio-video tapes of what happened in each classroom. This was done in order to determine whether the teachers' practices were consistent with what they said in the interviews. Paradoxes and inconsistencies were documented. The historical and political analysis of ECD illustrates the complex development of ECD in South Africa over the last few decades. It therefore also highlights and brings to the fore the complex journey that Grade R teachers had to navigate in adapting their practice to ever changing curriculum requirements. The empirical results show that there are inconsistencies between what selected teachers know and believe, and what they are implementing. However, "silent themes" which did not come to the fore in the focus group or individual interviews, were identified in the audiovideo tapes of classroom activities. Also, many "silent themes" indicate that there are numerous concerns, such as lack of proficiency in bridging the gap between theory and practice, regarding the implementation of numeracy in Grade R. It was found that many of the selected Grade R teachers struggle to implement numeracy in their classrooms, as they lack the skills and support to teach numeracy in a Grade R context.
Keywords: Teachers -- South Africa -- Attitudes; Numeracy -- Study and teaching (Elementary) -- South Africa; Teachers -- Training of -- South Africa; Mathematics teachers -- In-service training -- South Africa; Early childhood education -- South Africa -- History; Early childhood education -- South Africa -- Political aspects